Optimal Income Tax Rates for the Korean Economy - Yong Sung Chang; Sun-Bin Kim; Bo Hyun Chang (KDI Journal of Economic Policy, 2015)
Based on a quantitative, heterogeneous agent general equilibrium model, we compute the optimal tax rates for labor and capital incomes for the Korean economy. According to our model, a more progressive income tax schedule along with a higher capital tax rate can increase average welfare by as much as 0.86% of permanent consumption. Approximately 64% of house-holds, those with low assets and low productivity, are better off when a more progressive optimal tax schedule is adopted. Despite the potentially significant welfare gains, our calculation should be interpreted with caution because our benchmark model does not take into account possible capital outflows or the increased administrative costs associated with high taxes.
Keywords: E25; E62; H21; 330; Inequality; Korean Economy; Optimal Income Taxes; Progressivity Capital Tax